Analysis of systemic inflammatory and coagulation biomarkers in advanced cervical cancer: Prognostic and predictive significance. Issue 2 (June 2023) - Li, Ningfeng; Zhang, Yan; Qu, Wenjie; Zhang, Chao; Ding, Zhaoxia; Wang, Linlin; Cui, Baoxia
Objective: Peripheral systemic inflammatory, nutritional, and coagulation biomarkers have prognostic and predictive value in various malignancies. We evaluated the prognostic and predictive roles of systemic inflammatory, nutritional, and coagulation biomarkers in the circulating blood of patients with advanced cervical cancer. Methods: A retrospective study of 795 patients with cervical cancer who received concurrent chemoradiation therapy was performed. Overall survival was evaluated by the Kaplan–Meier estimator. Univariate and multivariate Cox regression models were used to determine prognostic factors associated with overall survival. Results: The median follow-up time was 76 months. In the univariate analysis, overall survival showed positive prognostic value in patients with a platelet-to-lymphocyte ratio (PLR) <164.29 ( P = 0.010), and a plasma fibrinogen (FIB) level <4 g/L( P = 0.012). In the multivariate analysis, the PLR ( P = 0.036), and FIB level ( P = 0.047) maintained their significance for overall survival. Therefore, the PLR and FIB levels are independent prognostic factors in patients with advanced cervical cancer. Conclusions: Systemic inflammatory and coagulation biomarkers could help to understand survival differences in the clinical treatment of advanced cervical cancer. The PLR and FIB levels are independent prognostic factors of poor survival in patients with advanced cervical cancer.